Uji Coba dan Validasi Aplikasi Etnobatik sebagai Media Pembelajaran Matematika Berbasis Android - Lestari, Mei; Rahayu, Wanti; Irawan, Ari (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2022)
This study aims to develop mathematics learning media using ethnomathematical elements in Javanese batik which are called an android-based ethnobatic application. Ethnobatics is an android-based learning application designed to be used in learning mathematics combined with Javanese batik culture to increase students' interest and understanding in learning mathematics by relating everyday realities through Javanese batik motifs. The research method used in this study is RnD (Research and Development) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The data collection technique used in this study was a questionnaire instrument to test the validity of the application used for expert validators and elementary school students as users. The results of this study indicate that the android-based ethnobatic application can be used as a medium for learning mathematics based on the assessment of expert validators and also the assessment of students in the use of ethnobatic applications in mathematics learning activities.